2018
DOI: 10.1055/s-0038-1641750
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein M Protects Lipopolysaccharide-Treated Mice from Death and Organ Injury

Abstract: These results suggest that apoM possesses protective properties against LPS-induced organ injuries and could potentially be introduced as a novel therapy for the severe conditions that are consequent to sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…The ApoM KO mice were produced as described in the previous report [ 17 ], and the blood samples were collected from 10-week-old male KO mice and WT mice, which were subjected to a 6-h fast. The plasma samples were separated into HDL and Lp-dep fractions, and the S1P and DH-S1P levels were measured.…”
Section: Methodsmentioning
confidence: 99%
“…The ApoM KO mice were produced as described in the previous report [ 17 ], and the blood samples were collected from 10-week-old male KO mice and WT mice, which were subjected to a 6-h fast. The plasma samples were separated into HDL and Lp-dep fractions, and the S1P and DH-S1P levels were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2011, when ApoM was first ABBREVIATIONS: ApoM, apolipoprotein M; BW, body weight; Col, collagen; Ctgf, connective tissue growth factor; FBS, fetal bovine serum; Fn, fibronectin; GFP, green fluorescent protein; HIGA, hyper-IgA; KO, knockout; PAS, periodic acid-Schiff; PTX, pertussis toxin; rApoM, recombinant ApoM; S1P, sphingosine 1-phosphate; siApoM, small interfering RNA against murine ApoM; siCtl, control siRNA; WT, wild type established as a carrier of S1P (25), we and others have demonstrated that ApoM is not actually a carrier of S1P, but rather is a modulator of S1P metabolism, and S1P bound to albumin is unstable in plasma, whereas S1P bound to ApoM is stable (30)(31)(32). We were able to modulate the plasma S1P levels continuously using the adenoviral gene transfer of ApoM or the knockdown of ApoM in an in vivo siRNA system (33,34). The epidemiologic association between HDL and the progression of chronic kidney diseases also prompted us to investigate the association between S1P and IgA nephropathy (35,36).…”
mentioning
confidence: 89%
“…For the experiments investigating cell proliferation, MES13 cells were cultured on a 96‐well plate at a concentration of 2000 cells/well overnight. The medium was replaced with an FBS‐free medium containing the vehicle or 10 µM VPC, 10 µM JTE, or pertussis toxin (PTX, P7208; MilliporeSigma) at 20 ng/ml for 2 h. Then, the medium was replaced with an FBS‐free medium containing pharmacological inhibitors with various concentrations of S1P bound to 0.004% w/w fatty acid‐free albumin or recombinant ApoM (rApoM; R&D Systems, Minneapolis, MN, USA) or with HDL collected from 10‐wk‐old wild‐type C57BL/6 (WT) mice or ApoM‐knockout C57BL/6 (KO) mice, described in a previous paper (34), at a concentration of 0.25 mg protein/ml. In detail, we prepared S1P bound to albumin or recombinant ApoM as follows; S1P (Enzo Life Sciences, Plymouth Meeting, PA, USA) was dissolved in methanol.…”
Section: Histologic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Apolipoprotein M is a 25-kDa protein contained in about 5% of HDL particles that can bind sphingosine 1-phosphate (S1P, see below), whose concentration is drastically decreased in sepsis and inflammatory conditions [29]. Apolipoprotein M (ApoM) was shown to limit LPS-induced acute lung injury [30], as well as mortality in LPS-treated mice [31].…”
Section: Hdl Proteomementioning
confidence: 99%